2015
DOI: 10.1021/acs.iecr.5b00482
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Sensor Placement for Fault Diagnosis Using Magnitude Ratio

Abstract: Major performance losses occur in process industries due to failures that are not identified at the incipient stage.Early detection of such faults is also critical for the safety of the equipment, operating personnel, and other resources. When a fault occurs in a system, it can propagate and affect several process variables. Variables that need to be measured in order to detect and diagnose the faults have to be identified and chosen economically. An algorithmic approach for identifying the optimal number, typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In [12], position optimization of sensors method based on bond graph to digraph transformation for the small modulus gear life experiment of a spacecraft was proposed. Mobed et al [13] integrated the magnitude ratio and the fault evolution sequences and proposed an optimization algorithm for sensor location, type and number. The above research on the sensitive measuring points concentrated upon the sensor location optimization of the complete machine, and the impact from sensitivities of measuring point to fault diagnosis still exists.…”
Section: Bearing Vibration Signals Contain a Wealth Of Information Aboutmentioning
confidence: 99%
“…In [12], position optimization of sensors method based on bond graph to digraph transformation for the small modulus gear life experiment of a spacecraft was proposed. Mobed et al [13] integrated the magnitude ratio and the fault evolution sequences and proposed an optimization algorithm for sensor location, type and number. The above research on the sensitive measuring points concentrated upon the sensor location optimization of the complete machine, and the impact from sensitivities of measuring point to fault diagnosis still exists.…”
Section: Bearing Vibration Signals Contain a Wealth Of Information Aboutmentioning
confidence: 99%
“…Sensor placement has been carried out for different objectives, such as parameter estimation, state estimation, and fault detection. , Most sensor placement techniques optimize a performance criterion. Many contributions in the literature can be found that consider the steady-state behavior of the systems, including the sensor placement by qualitative analysis. , In the existing literature, many works on sensor placement belong to linear distributed parameter systems (DPS). Distributed parameter systems represent the dynamical systems governed by partial differential equations (PDEs).…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive reviews about the variety of methods proposed to locate instruments with fault diagnosis purposes have been presented. The instrumentation selection strategies for processes to be monitored using PCA satisfy at least the observability and resolution of a predetermined set of faults. In this way, the detection and isolation of those failures are partially ensured. , It has been suggested to select sensors at the design stage by applying directed-graph-based procedures or a technique that assumes the fault probability values for the instruments and the process .…”
Section: Introductionmentioning
confidence: 99%